An ontology and a REST API for sequence based microbial typing data - Almeida, João (2021)
In the Microbial typing field, the need to have a common understanding of the concepts described and the ability to share results within the community is an increasingly important requisite for the continued development of portable and accurate sequence-based typing methods. These methods are used for bacterial strain identification and are fundamental tools in Clinical Microbiology and Bacterial Population Genetics studies. In this article we propose an ontology designed for the microbial typing field, focusing on the widely used Multi Locus Sequence Typing methodology, and a RESTful API for accessing information systems based on the proposed ontology. This constitutes an important first step to accurately describe, analyze, curate, and manage information for microbial typing methodologies based on sequence based typing methodologies, and allows for the future integration with data analysis Web services.